2014
DOI: 10.1016/j.jchf.2013.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Size and Sex-Matching in Heart Transplantation

Abstract: Objective This study evaluated whether worsened outcomes in sex mismatch are related to mismatch of organ size in heart transplantation. Background Sizing for organ allocation in heart transplantation currently incorporates only body weight differences between the donor and recipient. Weight correlates poorly to cardiac size, and donor–recipient weight differences are not associated with differential survival. Heart size correlates with sex, and donor–recipient sex mismatch conveys worse-than-expected outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(85 citation statements)
references
References 21 publications
1
81
2
1
Order By: Relevance
“…Worse survival in the male-mismatch patients is usually attributed to weight-mismatch or size-mismatch, in which the heart from a smaller female donor cannot meet the cardiac demands of the larger male recipient. 18,24 However, only 1 study reported worse survival in the female-mismatch HT patients but not in the male-mismatch patients, 10 as our study found.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Worse survival in the male-mismatch patients is usually attributed to weight-mismatch or size-mismatch, in which the heart from a smaller female donor cannot meet the cardiac demands of the larger male recipient. 18,24 However, only 1 study reported worse survival in the female-mismatch HT patients but not in the male-mismatch patients, 10 as our study found.…”
Section: Discussionmentioning
confidence: 42%
“…Higher post-HT mortality has been reported in both types of gender-mismatch in 8 articles, 2–9 only in the female-mismatch patients (male donor/female recipient) in 1 article, 10 and only in the male-mismatch patients (female donor/male recipient) in 14 articles. 11–24 However, 2 studies found no difference in HT mortality due to gender-mismatch of either kind.…”
Section: Introductionmentioning
confidence: 99%
“…Males with female hearts have maximal heart rate. This probably corresponds to heart size; male recipients/females donors are mostly undersized in heart size and have the shortest survival [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…41,42 Ideal donor/recipient body mass index (BMI) ratios within 20–30% are the generally accepted criteria. 43 The selection of a pig graft that is appropriately size-matched to a particular recipient, eg, one who is rapidly deteriorating, may thereby conserve the supply of allografts and potentially optimize posttransplant outcome.…”
Section: Heart Xenotransplantationmentioning
confidence: 99%